MY SAY: The brave new world - Abd Razak, Dzulkifli (2008)
A hungry dog is loitering on the beach near a fishing village when suddenly one of its hind legs gets caught in driftwood. As the dog struggles to free its leg, a boy passes by. Scene 1 The dog pleads to the boy: "Can you please help release my hind leg from the driftwood?" The boy replies: "Why should I? You have been stealing a lot of fish from the villagers lately." Dog: "Please, the driftwood is hurting my leg. If you help me, I will not steal again. Don't you know that the dog is man's best friend?"